Polyclonal IgG Response of Balb/c Mice to the 23 kDa Antigen of Entamoeba histolytica - Santos, Herbert J.; Maiquilla, Sheena Marie B.; Rivera, Windell L. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 20 No 1 (2008), 2008)
Entamoeba histolytica is one of the most significant protozoan pathogens found in developing countries like the Philippines. This intestinal parasite causes the disease amebiasis, which has a yearly average mortality of about 100,000 people worldwide. Thus, it is essential to develop new diagnostic markers and possible treatment against this disease. The crude cell extract of E. histolytica , was used to induce polyclonal antibody response in mice. Balb/c mice were given immunizations of the prepared crude E. histolytica antigens for a period of twelve weeks. Indirect fluorescent antibody test showed the specificity of polyclonal IgG in recognizing the cytosolic components of E. histolytica trophozoites. Enzyme-linked immunosorbent assay was performed to determine the antibody titers in sera collected at various time intervals. Antibody titers for the mouse serum taken 10 and 20 days after the third booster immunization were known to be 16,384 and 4,096 respectively. SDS-PAGE profile of the crude E. histolytica antigens revealed three bands with molecular weights of 23, 41, and 47 kDa. Western immunoblot results indicated that the polyclonal IgG produced by mice targets the potentially novel 23 kDa antigen from an axenic E. histolytica culture.
Keywords: amebiasis, < i> Entamoeba histolytica< /i> , IgG, immunoblot, indirect fluorescent antibody test, polyclonal antibodies